Serum Hsa_circ_0023919 is a Predictive Biomarker of Chemoresistance in CRC Treatment - Zhang L; Fang C; Zhu W; Zhong W; Ye R (International Journal of General Medicine)
Lei Zhang,1 Chuanfa Fang,1 Weiquan Zhu,1 Wu Zhong,1 Rongqiang Ye2 1Department of Gastrointestinal Hernia, Ganzhou People’s Hospital, Ganzhou, Jiangxi, 341000, People’s Republic of China; 2Department of Hepatobiliary and Pancreatic Surgery, Ganzhou People’s Hospital, Ganzhou, Jiangxi, 341000, People’s Republic of ChinaCorrespondence: Rongqiang Ye, Department of Hepatobiliary and Pancreatic Surgery, Ganzhou People’s Hospital, No. 16 Meiguan Avenue, Zhanggong District, Ganzhou, Jiangxi, 341000, People’s Republic of China, Tel +86-07975889858, Email yerongqiang394@163.comBackground: The diversity of available chemotherapeutic modalities for colorectal cancer (CRC) entails the implementation of personalized therapeutic regimens to optimize patient outcomes. Currently, the clinical use of biological markers for treatment selection is inadequate to achieve individualization. Circulatory RNAs (circRNAs), which function as plasma biomarkers, play a critical role in regulating biological processes in different types of cancer.Methods: The samples (serum) were obtained from 80 CRC patients and 80 healthy individuals (controls) to assess the level of hsa_circ_0023919 via qRT-PCR analysis.Results: In findings, hsa_circ_0023919 has a positive association with the disease stage and is greatly elevated in chemoresistant CRC patients. In addition, the area under the curve for hsa_circ_0023919 was modest, and an increase in hsa_circ_0023919 expressions was linked with a decreased overall survival (OS) and progression-free survival (PFS). Serum hsa_circ_0023919 levels serve as a diagnostic indicator for chemoresistance in CRC.Conclusion: The findings suggested that hsa_circ_0023919 contributes to promoting chemoresistance in CRC patients. Consequently, it can be considered a potent therapeutic target for CRC treatment.Keywords: hsa_circ_0023919, biomarker, chemoresistance, CRC